Understanding physical activity in cancer patients and survivors: new methodology, new challenges, and new opportunities - Schrack, Jennifer A. (Cold Spring Harb Mol Case Stud, 2017)
Since the early 1990s, accumulating evidence has suggested that regular, sustained participation in physical activity may help prevent the onset and development of certain types of cancer. Given the worldwide incidence and prevalence of cancer, there is increasing interest in physical activity as a nonpharmacological intervention and prevention method. Moreover, the effectiveness of new and improved cancer therapies has also increased interest in the potential health benefits of physical activity during and after treatment. The development of wearable device technology (e.g., accelerometers) to monitor physical activity has created unprecedented opportunities to better understand the potential health benefits of physical activity in cancer patients and survivors by allowing researchers to observe, quantify, and define physical activity in real-world settings. This granular, detailed level of measurement provides the opportunity for researchers and clinicians to obtain a greater understanding of the health benefits of daily physical activity beyond the well-established benefits of “moderate-to-vigorous” physical activity and to tailor recommendations to a feasible level of activity for older and/or sicker patients and survivors. This article provides an overview of accelerometers, the potential benefits—and challenges—of using these devices in the research and clinical settings, and recommendations for future applications.